Effects of the Chinese Traditional Prescription Xiaoyaosan Decoction on Chronic Immobilization Stress-Induced Changes in Behavior and Ultrastructure in Rat Hippocampus - Liang, Yuan (Hindawi Publishing Corporation, 2013)
Xiaoyaosan (XYS) decoction has been widely used as a traditional medicine for treating stress and depression-related disorders in China for thousands of years. Aim of the Study. To observe the potential mechanism of XYS decoction's antidepressant-like effect in α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors related to synaptic plasticity in the hippocampus rats induced by chronic immobilization stress (CIS). Materials and Methods. Animals were randomly divided into five groups: (1) control group; (2) sham-operated group; (3) CIS group, in which rats were conducted CIS for 21 days; (4) XYS decoction treatment group; (5) 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) positive group, in which the amygdala of CIS rats was unilaterally microinjected with a competitive glutamate receptor antagonist, CNQX. After CIS for 21 days, the open field test (OPT) and elevated plus-maze test (EPM) were measured, the ultrastructure of hippocampus CA(1) subregion was observed by the electron microscopy; both the GluR1 and GluR2 mRNA level of AMPA receptor subunits in hippocampus CA(1) subregion were detected by real-time qPCR. Results. Rats subjected to CIS exhibited increases in time in central zone and decreases in total distance traveled in the OPT. In the EPM, they also showed decreases in center zone time and entries, open arm time and entries, and an increase in close arm time. Ultrastructural damage in the hippocampus CA(1) was also observed. XYS decoction and CNQX showed significant improvement behavioral changes and the ultrastructural damage of the hippocampus CA(1); XYS decoction also reversed CIS-induced decreases in GluR2 mRNA and increases in GluR1 mRNA in the hippocampus CA(1) as well as CNQX. Conclusions. XYS decoction may effectively produce an antidepressant-like effect, which appears to be involved AMPA receptors related synaptic plasticity of hippocampus.